Moderasi Corporate Social Responsibility Pada Pengaruh Profitabilitas Terhadap Nilai Perusahaan Pada Perusahaan Manufaktur - Pradnyana, Kadek Dwi Dharma; Dwiana Putra, I Made Pande (E-Jurnal Akuntansi; Vol 24 No 1 (2018), 2018)
Corporate value is a description of the company's performance. This study aims to know the effect of profitability to corporate value with Corporate Social Responsibility (CSR) as a moderating variable in manufacturing companies. This research was conducted by manufacturing companies that listed on the BEI in 2014-2016. The number of samples taken from 22 companies that produced 65 samples total. Data collection was done by non probability sampling method, especially purposive sampling method. Data analysis technique used Simple Linear Regression and Moderated Regression Analysis (MRA). Based on research results, it is known that profitability variable have positive effect to the firm value. The CSR variable strengthens the profitability effect on firm value. The presence of high CSR makes more investors believe that the company's performance in good condition, so that CSR becomes more valuable in the eyes of investors. Keywords: profitability, Corporate Social Responsibility , Corporate Values